Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Curar el pasado: teoría, curaduría y diálogo en una muestra de arte indígena contemporáneo del Gran Chaco Gualamba - Cantero, Emanuel (Memoria y Sociedad, 2018)
El siguiente artículo es una respuesta a la exposición de arte indígena contemporáneo Gran Chaco Gualamba. Arte, Cosmovisión, Soberanía (Chaco, Argentina; Julio de 2013). Sin desviarse de los propios objetivos de la muestra, problematiza la práctica curatorial como una forma de ver y mostrar a la producción artística de las poblaciones originarias como artefactos significantes íntimamente enlazados con sus formas de vida comunitaria -y no meramente obras de arte autónomas y asépticas de toda función social-. Contrastando las definiciones del equipo de curadoras, el corpus de obras expuestas y el discurso de pobladores originarios, se muestra que este intento por recuperar el nexo orgánico entre arte, cosmovisiones y vida en comunidad resulta trunco, dado que los propios pobladores originarios consideran esta vinculación como una circunstancia históricamente pretérita, previa a los procesos de colonización. Recuperando las luchas presentes de las comunidades, que a falta de ese pasado armonioso plantean su identidad como resistencia necesaria para un futuro distinto – mejor-. This work is a response to a contemporary indigenous art exhibition titled «Gran Chaco Gualamba - Arte, Cosmovisión, Soberanía» (Chaco, Argentina; July 2013). Consistent with the purposes of this exhibition, the article problematizes curatorial practice as a way to present the artistic production of the indigenous populations as significant artifacts intimately involved in the daily community life, and not merely as autonomous artistic objects with no social function. By contrasting the definitions provided by the curatorial team,the corpus of artworks exhibited and the native peoples’ speech, the article shows how the exhibit fails to recover the link between art, cosmovisions and community life because the native populations themselves consider these three spheres as an outdated historical circumstance, previous to the colonization processes. Finally, the current struggles of the communities are mapped which, in the absence of that harmonious past, pose their identity as a necessary resistance for a better future.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé